First language attrition, use and maintenance : the case of German Jews in anglophone countries - Schmid, Monika S. (Studies in bilingualism, 2002)
This book is a study of the L1 attrition of German among German Jews who emigrated to anglophone countries under the Nazi regime. It places the study of language attrition within the historical and sociocultural framework of Weimar and Nazi Germany, applying issues of identity and identification to first language loss and maintenance. Morphosyntactic features of German are looked at in free spoken discourse, in an analysis of both 'interferences' or 'errors' and their overall (correct) use. The picture of L1 proficiency which emerges from these investigations is then related to a taxonomy of i.